TypiCal but DeliCate Ca++re: Dissecting the Essence of Calcium Signaling Network as a Robust Response Coordinator of Versatile Abiotic and Biotic Stimuli in Plants - Patra, Neelesh; Hariharan, Shruthi; Gain, Hena; Maiti, Mrinal K.; Das, Arpita; Banerjee, Joydeep (Frontiers in Plant Science, 2021)
Plant growth, development and ultimately crop productivity are largely impacted by the plant’s interaction with different abiotic and biotic factors throughout its life cycle. Perception of different abiotic stresses like salt, cold, drought, heat and heavy metals as well as interaction with beneficial and harmful biotic agents by plants lead to transient, sustained, or oscillatory changes of [Ca2+]cyt within the cell. Significant progress has been made in decoding of Ca2+ signatures into downstream responses to modulate differential developmental and physiological responses in the whole plant. Ca2+ sensor proteins, mainly calmodulins (CaMs) and calmodulin-like proteins (CMLs) and others like Ca2+-dependent protein kinases (CDPKs), calcineurin B-like proteins (CBLs) and calmodulin-binding transcription activators (CAMTAs) have played the critical roles in coupling the specific stress stimulus with an appropriate response. This review summarises current understanding of Ca2+ influx and efflux system in plant cell and various Ca2+ binding protein-mediated signal transduction pathways that are delicately orchestrated to mitigate abiotic and biotic stresses. The probable interactions of different components of Ca2+ sensor relays and Ca2+ sensor responders in response to various external stimuli have been described diagrammatically focussing established pathways and latest developments. Present comprehensive insight into key components of Ca2+ signaling toolkit in plants can provide innovative framework for biotechnological manipulations towards crop improvability in near future.